(untitled) (Ukrainian Journal of Ophthalmology, 2025)
Filatov Memorial Lectures-2019, a research-to-practice conference with international participation, was held in Odesa on the 23rd -24th of May 2019. The event was organized by SI “The Filatov Institute of Eye Diseases and Tissue Therapy of the NAMS of Ukraine” and the Ukrainian Society of Ophthalmologists and supported by National Academy of Medical Science of Ukraine and Ministry of Health of Ukraine. This outstanding health care event combined an extensive relevant scientific and practical programme including 15 main sessions, 2 instructional courses, 3 industry-sponsored symposia, 5 workshops, and a poster presentation session, where over 110 Ukrainian and foreign specialists presented their innovations, inventions, and advances in the field of ophthalmology.